Pola Asuh Orangtua Berhubungan Dengan Perkembangan Sosial Anak Usia Pra Sekolah (4-6 tahun) - Ayuni Prihadiningtyas; Ni Wayan Dwi Rosmalawati; Jupriyono Jupriyono; Ida Prijatni (Poltekkes Kemenkes Malang & IBI Ranting Pendidikan Kota Malang, 2022)
The rate of growth and development delays at the preschool age is still quite high. This will pose risks at later stages of growth and development. At preschool age, it can be said as a period of child socialization. One of the factors that influence the social development of children is parenting. This study aims to determine the relationship between parenting and social development of preschool-aged children (4-6 years). This study used a correlation analytic design with a cross-sectional approach with a sample of 38 respondents selected by simple random sampling. Collecting data on parenting variables using a structured questionnaire and social development using a Vineland Social Maturity Scale (VSMS) questionnaire. Data analysis using Goodman and Kruskal Tau. The results showed that most parents applied democratic parenting (92.11%) and preschoolers had social development above the average (76.32%). The results of the analysis showed that there was a relationship between parenting patterns and children's social development (p-value of 0.001). Parents have an important role in nurturing and educating children to become socially mature individuals. Monitoring of children's social development needs to be done to diagnose developmental problems so that early treatment can be carried out and minimize the impact of delays in social development. Keywords: Parenting, Social Development, Preschool-Age Children